CrimRxiv 2021
DOI: 10.21428/cb6ab371.9f192284
|View full text |Cite
|
Sign up to set email alerts
|

What Does the Public Want Police to Do During Pandemics? A National Experiment

Abstract: We administered a survey experiment to a national sample of 1,068 US adults in April 2020 to determine the factors that shape support for various policing tactics in the midst of the COVID-19 pandemic. Respondents were sharply divided in their views about pandemic policing tactics, and were least supportive of policies that might limit public access to officers or reduce crime deterrence. Information about the health risks to officers, but not to inmates, significantly increased support for "precautionary" pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 79 publications
0
10
0
Order By: Relevance
“…The thermometer approach also is well suited for studying the influence of moral intuitions because, as described above, moral intuitions are conceptualized as operating via a “dual process” system in which “fast thinking,” intuitive moral cognitions, including feelings , precede and influence moral reasoning and position‐taking (Haidt, 2012). Although we are unable to examine police legitimacy (i.e., trust in the institution of policing and a corresponding felt obligation to obey the police) and procedural justice (i.e., perceptions of fairness and care in police conduct; Nix et al., 2021; Silver, 2020; Sunshine & Tyler, 2003; Tankabee, 2013; Tyler, 2006; Wolfe et al., 2016), we recognize that respondents’ positive feelings toward police are likely to correlate with both of these well‐studied factors, thus suggesting additional avenues for theoretical development based on our results (we return to this point in the Discussion).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The thermometer approach also is well suited for studying the influence of moral intuitions because, as described above, moral intuitions are conceptualized as operating via a “dual process” system in which “fast thinking,” intuitive moral cognitions, including feelings , precede and influence moral reasoning and position‐taking (Haidt, 2012). Although we are unable to examine police legitimacy (i.e., trust in the institution of policing and a corresponding felt obligation to obey the police) and procedural justice (i.e., perceptions of fairness and care in police conduct; Nix et al., 2021; Silver, 2020; Sunshine & Tyler, 2003; Tankabee, 2013; Tyler, 2006; Wolfe et al., 2016), we recognize that respondents’ positive feelings toward police are likely to correlate with both of these well‐studied factors, thus suggesting additional avenues for theoretical development based on our results (we return to this point in the Discussion).…”
Section: Methodsmentioning
confidence: 99%
“…The study found that binding moral intuitions were positively associated with perceptions of police legitimacy and acceptance of police use of force, and that individualizing moral intuitions were inversely associated with these outcomes. In the second study, Nix et al (2021) found that MFT's Authority/subversion foundation (the only moral foundation measured) was negatively associated with respondents' support for "precautionary policing" during the Covid-19 pandemic, which involved cutting back on traditional policing activities to reduce virus spread. Neither Silver (2020) nor Nix et al (2021) examined attitudes toward BLM; nor did they examine the role of systemic racism beliefs in predicting and mediating attitudes toward BLM or police.…”
Section: Moral Intuitions and Attitudes Toward Blm And Policementioning
confidence: 97%
See 1 more Smart Citation
“…In the COVID-19 context, research has also found that perceptions of the procedurally just nature of authorities' treatment toward community members can improve public willingness to comply with authorities' directives (see, e.g. McCarthy et al , 2021; Nix et al. , 2021; Sandrin and Simpson, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has highlighted important policing issues to consider during the COVID-19 pandemic (Lum et al , 2020; Nix et al , 2020; Stogner et al , 2020). Brooks and Lopez (2020) described ideal ways for the police to respond during the COVID-19 emergency.…”
Section: Literaturementioning
confidence: 99%